Detection of Palmer amaranth (Amaranthus palmeri) and large crabgrass (Digitaria sanguinalis) with in situ hyperspectral remote sensing. I. Effects of weed density and soybean presence. Issue 2 (24th March 2022) - Basinger, Nicholas T.; Hestir, Erin L.; Jennings, Katherine M.; Monks, David W.; Everman, Wesley J.; Jordan, David L.
Abstract: The utilization of remote sensing in agriculture has great potential to change the methods of field scouting for weeds. Previous remote sensing research has been focused on the ability to detect and differentiate between species. However, these studies have not addressed weed density variability throughout a field. Furthermore, the impact of changing phenology of crops and weeds within and between growing seasons has not been investigated. To address these research gaps, field studies were conducted in 2016 and 2017 at the Horticultural Crops Research Station near Clinton, NC. Two problematic weed species, Palmer amaranth ( Amaranthus palmeri S. Watson) and large crabgrass [ Digitaria sanguinalis (L.) Scop.], were planted at four densities in soybean [ Glycine max (L.) Merr.]. Additionally, these weed densities were grown in the presence and absence of the crop to determine the influence of crop presence on the detection and discrimination of weed species and density. Hyperspectral data were collected over various phenological time points in each year. Differentiation between plant species and weed density was not consistent across cropping systems, phenology, or season. Weed species were distinguishable across more spectra when no soybean was present. In 2016, weed species were not distinguishable, while in 2017, differentiation occurred at 4 wk after planting (WAP) and 15 WAP when weeds were present with soybean. When soybean was not present, differentiation occurred only at 5 WAP in 2016 and at 3 WAP through 15 WAP in 2017. Differentiation between weed densities did occur in both years with and without soybean present, but weed density could be differentiated across more spectra when soybean was not present. This study demonstrates that weed and crop reflectance is dynamic throughout the season and that spectral reflectance can be affected by weed species and density.